BRTO for ectopic small intestinal varices bleeding via dilated superior mesenteric veins and left ovarian vein: A case report - Yu You; Weicheng Wang; Jiawei Zhong; Sihai Chen (Radiology Case Reports)
Ectopic Variceal Bleeding is a rare complication of portal hypertension, often difficult to manage and potentially life-threatening. However, established guidelines directing treatment are lacking. This report presents a 51-year-old female with hepatitis B-related cirrhosis, who experienced rare small intestinal bleeding due to varicose veins in the superior mesenteric vein and left ovarian vein. The bleeding was successfully resolved by Balloon-occluded Retrograde Transvenous Obliteration. This report discusses the feasibility of BRTO compared to Transjugular Intrahepatic Portosystemic Shunt for certain patients with EctVB.